Simulasi Sistem Hibrid Pembangkit Energi Surya, Angin, dan Generator Untuk Mengoptimalkan Pemanfaatan Daya Energi Terbarukan - Hendrayana Hendrayana (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Electrical energy crisis related to the increasing population in an area will increase the electrical energy customers. Besides diminishing reserves of fossil energy that is required of alternative energy from renewable energy sources. The problem is in incorporating a potential source of renewable energy with a generator needs power generation hybrid, the hybrid system with a generator as backup energy utilization is less than optimal because when there was a deficit power generator takes over all of the power wasted in renewable energy generation. The purpose of study is to produce a hybrid system design between the generation of solar energy, wind energy and generator as support (support) when the power deficit in energy of renewable generator. Research Method in the design of hybrid system is a design block diagram consisting of solar panels, wind turbines, inverters, and generator. At this stage it has produced research outputs in the form of models of hybrid renewable energy generation systems and generators, then make a circuit simulation and measurement. The results of this research is a hybrid system that works adaptive- connected the generator to the system when the power deficit or increase the load to provide power support on renewable energy generation. This hybrid system with a capacity of 3.5 kW less power than the previous system with the composition generator 5.7 kW 2.2 kW of renewable energy consists of a 1 kW solar panels, wind turbines 1.3 kW and 1.3 kW generator voltage at 310V DC bus coupling, the voltage on the bus coupling AC 220V / 50 Hz, total load current at 16A. The percentage utilization of renewable energy rose from 11.73% to 24,94% and generator utilization fell from 24.50% to 16.74%.